Identification, characterization and evaluation of honeybee floras in Kafa, Sheka and Benchi Maji Zones of Southern Nations Nationalities and Peoples Region (SNNPR), Ethiopia - Tesfu Shegaw; Dawit Habte Giorgis (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The study was aimed with identifying and characterizing honeybee floras and their flowering seasons in south western parts of the country. Relevant data were collected through conducting questionnaire survey, focus group discussions, field observations and lab analysis of pollen and honey samples. In addition, seasonal performance of colonies in terms of brood area, adult population, pollen and nectar stores were evaluated. The obtained data were analyzed using SPSS-ver.20 and MsExcels. Accordingly, a total of 200floral species categorized under 77families identified. Of which, 26(13%) grouped under 16 families characterized as major bee floras. Seasons, January to February, July to August were considered as Dearth periods; March, September to October were brooding seasons, April, November to December were major nectar flow seasons. March to April and November to December were major honey flow seasons being the first for high land and mid land areas and the later for lowland areas whose major botanical origin was Schefflera abyssinica and Guizetia scabra respectively. However, in some areas with better forest covers, Manilkara butij become a major honey source plant. Whereas, January, June to July, March (in low lands) were considered as minor/mini harvesting seasons whose major botanical origin was Vernonia species, Croton macrostachyus and Combritum species respectively. It was noted that there was a significant correlation among brood area, adult population, pollen store and nectar stores at p<0.01.